Description of Methodology for Testing the Synergistic and Additive Effects of Antibiotics in Vitro - Kmiecikowski Paweł Z.; Gabriel Aniela; Depka Dagmara; Bogiel Tomasz (Postępy Mikrobiologii)
Given the dynamic growth of antibiotic resistance observed over the past few decades, new therapeutic methods for life-threatening infections are crucial. Effective treatment of infections caused by multidrug-resistant microorganisms increasingly requires the use of last resort drugs, and new antibiotics generate resistance in less time than it takes to bring them to the therapy. Therefore it is advisable to seek solutions using currently available antibiotics. Effective therapy of infections with multidrug-resistant microorganisms may be enabled by the use of additive and synergistic interactions, resulting from the combination of different groups of antibiotics with the same or different modes of action – including those to which a particular bacterial strain is resistant. This paper describes methods for determining the synergistic and additive effects of antibiotics in vitro, including the CombiANT method under testing. The purpose of this study is to present possible methods for determining the additive and synergistic effects between antibiotics in vitro and to propose appropriate laboratory procedures for their use. This paper reviews the latest literature on methods for determining the antimicrobials interactions. Clinical studies indicate significant benefits of using the phenomenon of antibiotic addition or synergy in clinical practice, not only improving the effectiveness of therapy, but also minimizing side effects and reducing the risk of developing de novo antibiotic resistance. Despite the significant problem of increasing antibiotic resistance level, clinical practice still lacks clearly standardized methods for determining synergism. Further research is needed to determine the most beneficial standard available for a wide range of microbiology diagnostic facilities.